Handling your ups and downs : a children's book about emotions - Berry, Joy Wilt.; Hergenroeder, Ernie (Waco, Tex. : Educational Products Division, Word, inc., 1979)
Discusses emotions and suggests ways to handle the comfortable and uncomfortable feelings everyone periodically has.
Keywords: Emotions -- Juvenile literature; Emotions